2016
DOI: 10.2337/dc15-2011
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study Among 27,482 Women

Abstract: OBJECTIVETo examine the association between age at menarche and risk of gestational diabetes mellitus (GDM).RESEARCH DESIGN AND METHODSA prospective cohort study of 42,109 eligible pregnancies from 27,482 women in the Nurses’ Health Study II.RESULTSThe adjusted risk ratios for GDM across the age at menarche categories (≤11, 12, 13, and ≥14 years) were 1.34 (95% CI 1.14–1.58), 1.13 (0.97–1.31), 1.11 (0.95–1.29), and 1.00 (referent; P for trend = 0.0005), respectively. Analysis of the mediating effect indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
0
35
1
Order By: Relevance
“…2Forest plot of the relative risks for GDM in women with an AAM ≤ 11 years relative to that of women with an AAM of 13 years in citations [1315, 17, 18], respectively …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2Forest plot of the relative risks for GDM in women with an AAM ≤ 11 years relative to that of women with an AAM of 13 years in citations [1315, 17, 18], respectively …”
Section: Resultsmentioning
confidence: 99%
“…(13 years)0.8 (0.5, 1.3) (14 years)1.2 (0.8, 1.8) (> = 15 years)Self-reported AAM, only included English speakers/readersChen et al [13], U.S.A12.634.1Nurses’ Health Study II, largely white cohort of nurses1404 out of 42109 pregnancies, self-reported GDM in any of their previous pregnancies1.3 (1.1, 1.5) (<= 11 years)1.0 (0.9, 1.2) (12 years)Ref. (13 years)0.9 (0.8, 1.0) (>= 14 years)All participants were nurses, self-reported AAM, self-reported GDMLi et al [14], China13.128.5Healthy Baby Cohort Study, Chinese birth cohort1015 out of 6900 pregnancies, week 2428 75g OGTT using IADPSG criteria [29]1.4 (1.1, 1.7) (<= 11 years)1.1 (0.9, 1.3) (12 years)Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 included studies [ 11 15 ] were all cohort studies, with sample sizes ranged from 3,490 to 27,482 women. Of these prospective studies, three were conducted in the United States [ 11 , 12 , 15 ], one in Australia [ 14 ] and one in China [ 13 ]. In all studies, age at menarche was self-reported and grouped into 5 categories, with the exception of two studies [ 11 , 15 ].…”
Section: Resultsmentioning
confidence: 99%